2022
DOI: 10.48550/arxiv.2201.05045
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sensitivity of superconducting states to the impurity location in layered materials

Bastian Zinkl,
Aline Ramires

Abstract: The family of multi-layered superconductors derived from the doped topological insulator Bi2Se3 has been found to be unusually robust against non-magnetic disorder. Recent experimental studies have highlighted the fact that the location of impurities could play a critical role for this puzzling robustness. Here we investigate the effects of four different types of impurities, on-site, interstitial, intercalated and polar, on the superconducting critical temperature. We find that different components of the sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Before starting the discussion on nonunitary superconductivity, it is useful to introduce the concept of superconducting fitness [49,50], as this is going to be a key ingredient in the analysis that follows. The superconducting fitness framework has been a useful theoretical tool allowing for the understanding of the stability and nodal structure of unexpected superconducting states [8,[51][52][53], the robustness of unconventional superconducting states in the presence of impurities [4,54], and the unusual behavior of complex superconductors under external symmetry breaking fields, such as strain [55]. This seems to be one of the most appropriate frameworks for the description of superconductivity in complex quantum materials, allowing for the understanding of apparently contradicting responses of complex superconductors.…”
Section: The Concept Of Superconducting Fitnessmentioning
confidence: 99%
“…Before starting the discussion on nonunitary superconductivity, it is useful to introduce the concept of superconducting fitness [49,50], as this is going to be a key ingredient in the analysis that follows. The superconducting fitness framework has been a useful theoretical tool allowing for the understanding of the stability and nodal structure of unexpected superconducting states [8,[51][52][53], the robustness of unconventional superconducting states in the presence of impurities [4,54], and the unusual behavior of complex superconductors under external symmetry breaking fields, such as strain [55]. This seems to be one of the most appropriate frameworks for the description of superconductivity in complex quantum materials, allowing for the understanding of apparently contradicting responses of complex superconductors.…”
Section: The Concept Of Superconducting Fitnessmentioning
confidence: 99%
“…Before staring the discussion on nonunitary superconductivity, it is useful to introduce the concept of superconducting fitness [31,32], as this is going to be a key ingredient in the analysis that follows. The superconducting fitness framework has been a useful theoretical tool allowing for the understanding of the stability and nodal structure of unexpected superconducting states [33,34,35,36], the robustness of unconventional superconducting states in the presence of impurities [4,37], and the unusual behaviour of complex superconductors under external symmetry breaking fields, such as strain [38]. This seems to be one of the most appropriate frameworks for the description of superconductivity in complex quantum materials, allowing for the understanding of apparently contradicting responses of complex superconductors.…”
Section: The Concept Of Superconducting Fitnessmentioning
confidence: 99%
“…The gap is measured in units of the topological gap for the topological pristine system ∆ T . In particular, it is observed that the location of the impurity strongly impacts the gap of the system 87 . The resulting gap of the defective system can range from the pristine value, observed for impurities at the exchange maximum, to nearly zero, observed for impurities away from the exchange maximum (Fig.…”
Section: Strong Impurities In Topological Moire Superconductorsmentioning
confidence: 99%